2016
DOI: 10.1159/000453265
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Drug Hypersensitivity into Allergic, p-i, and Pseudo-Allergic Forms

Abstract: Drug hypersensitivity reactions (DHR) are clinically and functionally heterogeneous. Different subclassifications based on timing of symptom appearance or type of immune mechanism have been proposed. Here, we show that the mode of action of drugs leading to immune/inflammatory cell stimulation is a further decisive factor in understanding and managing DHR. Three mechanisms can be delineated: (a) some drugs have or gain the ability to bind covalently to proteins, form new antigens, and thus elicit immune reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 59 publications
1
129
1
6
Order By: Relevance
“…This phenotype typically includes the mast cell activation IgE mediated endotype, driven by epitope-specific IgE with mast cells as the main players. Other endotypes include direct complement activation [1,18], HSRs mediated by cyclooxygenase-1 inhibition in Aspirin Exacerbated Respiratory Disease (AERD) and Aspirin Exacerbated Cutaneous Disease (AECD) [19,20], or reactions due to some drugs with THIQ (tetrahydroisoquinoline)motifs which signal through the human G-protein-coupled receptor (MrgprX2) may also induce histamine release are included in the mast cell activation endotype [21,22]. In the past, symptoms such as fever, chills, and pain were not typically associated with allergic reactions, however, they have been reported during HSRs to monoclonals, oxaliplatin, and taxanes [3,6,9,23].…”
Section: Drug Hypersensitivity Reactions: New Clinical Approach Thmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype typically includes the mast cell activation IgE mediated endotype, driven by epitope-specific IgE with mast cells as the main players. Other endotypes include direct complement activation [1,18], HSRs mediated by cyclooxygenase-1 inhibition in Aspirin Exacerbated Respiratory Disease (AERD) and Aspirin Exacerbated Cutaneous Disease (AECD) [19,20], or reactions due to some drugs with THIQ (tetrahydroisoquinoline)motifs which signal through the human G-protein-coupled receptor (MrgprX2) may also induce histamine release are included in the mast cell activation endotype [21,22]. In the past, symptoms such as fever, chills, and pain were not typically associated with allergic reactions, however, they have been reported during HSRs to monoclonals, oxaliplatin, and taxanes [3,6,9,23].…”
Section: Drug Hypersensitivity Reactions: New Clinical Approach Thmentioning
confidence: 99%
“…Recent studies have shown that small molecule drugs may induce systemic non-IgE mediated reactions through the activation of human MC G-protein coupled receptor (MrgprX2) [21,22]. The IgE mediated pathway is the one that is best defined: patients who are predisposed to developing an allergic reaction switch their allergen specific antibodies from IgM to IgE after several exposures.…”
Section: Mast Cells: Positive and Negative Regulation Is Relevant mentioning
confidence: 99%
“…A strong relationship between ATRA and skin mast cells has been confirmed, as mast cell‐deficient Kit W‐sh/W‐sh mice did not show as serious dermatitis as WT mice . Mast cell‐mediated drug hypersensitivity mainly consists of allergic/immune reaction, pharmacological interaction with immune receptors (p‐i reactions), and pseudoallergy . The most frequent form is the IgE‐mediated type I allergic reaction, which occurs rapidly and is induced by antigens via prior exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Three distinct ways by which stimulation of immune or inflammatory cells associated with typical clinical manifestations, time of appearance, dose dependence, predictability, and cross-reactivity have been identified: (a) an allergic/immune reaction; (b) pharmacological interaction with immune receptors (P-I reactions), and (c) pseudo-allergic reaction (Fig. 2) [81]. Multiple drug hypersensitivity is characterized by long-lasting hypersensitivity reactions to different drugs as a consequence of a massive T cell stimulation that first presents with exanthema or drug rash with eosinophilia and systemic symptoms, while upon the second stimulus, erythroderma, Stevens-Johnson syndrome/toxic epidermal necrolysis, hepatitis, and agranulocytosis may develop [82].…”
Section: Drug Hypersensitivity: the Triad Of Pathomechanism Diagnostmentioning
confidence: 99%